Challenges ahead: Long-term perspectives of the German economy - Karl-Heinz Paqué; Rüdiger Soltwedel; Holger Schmieding; Ulrich Hiemenz; Rolf J. Langhammer; Henning Klodt; Jörg-Volker Schrader; Joachim Scheide; Ernst-Jürgen Horn; Karl-Heinz Paqué; Alfred Boss; Rainer Schmidt; et al. (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1993)
Table of Contents: I. External Challenges 12 1. The Transformation of Central and Eastern Europe 12 a. Trends in Central and Eastern Europe's Emerging Market Economies (EMEs) 12 b. The Impact on Germany 14 c. Political Consequences 14 2. Migration Pressures 16 a. The European Perspective 16 b. The German Perspective 18 c. Some Policy Issues 21 3. The Multilateral Trading System 22 a. Rising Tide of Protectionism 22 b. The German Trade Policy Stance 23 c. Perspectives 24 4. Industrial Policy 25 a. The Recent Controversy 25 b. The Record of Interventions 27 c. Future Prospects 28 5. The Adjustment of Agriculture 29 a. Global Prospects 29 b. The Reform of the Common Agricultural Policy (CAP) 30 6. European Integration 32 a. Monetary Union 32 b. Financial Markets 34 c. EC Initiatives on Social Policy 36 II. Internal Challenges 40 1. German Unification 40 a. The Rising Fiscal Burden 40 b. Economic Dualization 41 c. Digression: The "Treuhand" Record and Prospects 42 d. New Regional Growth Patterns 43 e. Political Pragmatism 45 2. Demography and the Welfare State 46 a. Facts and Forecasts 46 b. Implications for the Welfare State 50 3. Labour Markets and Collective Bargaining 52 a. Trends and Developments 52 b. The Future of Unionism 53 HI. Resources and Infrastructure 55 1. Energy and the Environment 55 a. Energy and Environmental Policy in the EC and in Germany 55 b. The Eastern German Energy Market and Environmental Targets 57 2. Transport 57 a. General Trends in Europe 57 b. The German Situation 59 c. Policy: Consensus and Controversies 60 d. Supranational Matter: The Role of the EC 61
Keywords: 330; Wirtschaftspolitik; Wirtschaftsprognose; Deutschland